Transformacje semantyczno-stylistyczne w rosyjskim języku literackim XVIII–XXI wieku - Николаева, Татьяна; Шишова, Анна (Studia Rossica Posnaniensia, 2016)
Investigating the semantic and stylistic transformations of the meaningful language units functioning in a given epoch allows us to show the internal regularities of their evolution, their systemic nature, and conditionality on factors of a historically cultural character. Realizating the semantic potential of a word capable of the associative rethinking plays an important role in the organization of modern vocabulary.